Research on coal pillar width and stability control for driving along goaf under hard roofs - CHEN Yun (Gong-kuang zidonghua)
Controlling large deformations of surrounding rock in driving along goaf under hard roofs is a technical challenge for safe and efficient underground coal mining. Currently, studies on determining coal pillar width in driving along goaf and surrounding rock stability control under thick-hard roofs fail to thoroughly discuss the influencing factors on pillar stability, especially neglecting the transmission effects of rotational deformation pressure from key block B in the main roof. To address this issue, a mechanical model for coal pillar width under a thick-hard roof was established, with the 90302 haulage roadway in Limin Coal Mine as the engineering background. The model yielded an optimal pillar width of 6.93 m. Considering engineering geological conditions and construction factors, the coal pillar width in driving along goaf for the 90302 haulage roadway was determined to be 7 m. The influence patterns of key block B in the main roof on coal pillar stability were analyzed, including its length, immediate roof stability coefficient, immediate roof thickness, and rotation angle. The coal pillar stability coefficient decreased with a increase in the length of key block B, and increased with an increase in the immediate roof stability coefficient and thickness, and an increase of the friction angle and cohesion within the coal seam. A Universal Distinct Element Code (UDEC) numerical calculation model was also developed to further analyze the influence patterns of key block B length on the deformation, fracture damage degree, and roadway failure characteristics of the 7-meter wide coal pillar. It was found that when key block B was 16 meters long, the two sides and the roof of the 90302 haulage roadway exhibited nearly symmetrical deformation without evident fractures, indicating a high degree of surrounding rock stability. To ensure surrounding rock stability and safe use of 90302 haulage roadway, hydraulic fracturing roof-cutting and pressure-relief control technology was adopted for the side suspended roof of key block B in the main roof. The practical application results demonstrated that surrounding rock deformation stabilized within 28 days after roadway excavation. During the mining period, the maximum roof-to-floor convergence reached 148 mm, and the maximum convergence of the two sides was 196 mm, guaranteeing the safe and effective mining of the working face.